PENGARUH FINANCIAL DISTRESS DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI PADA MASA PANDEMI COVID-19 (STUDI EMPIRIS PADA PERUSAHAAN JASA SUB SEKTOR RESTORAN, HOTEL, DAN PARIWISATA YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Youlanda Silvia Irawan; Kiagus Andi; Widya Rizki Eka Putri (Jurnal Akuntansi Bisnis dan Ekonomi, 2021)
The purpose of this study is to analyze the impact of financial distress and leverage on the conservatism of accounting. Samples of this survey are Hotels, Restaurants and Tourism sub-sectors listed on the Indonesian Stock Exchange during the covid-19 period.Using a purposive sampling method, the sample for this study comprised a sample of 32 hotels, restaurants, and tourism subsectors. The explanatory variables used in this study were accounting conservatism, financial distress, leverage, and profitability as control variables. In this study, we test using the Statistical Product and Service Solution (SPSS) analytical tools and data. The analysis in this study uses multiple linear regression analysis. The results of this study show that financial distress does not affect accounting conservatism and leverage does not affect accounting conservatism. Variables of the combination of financial distress and leverage have a significant impact on accounting conservatism.